Pemberdayaan Blogger sebagai Mitra Strategis dalam Peningkatan Branding dan Pemasaran UMKM Martabak: Studi Kasus Usaha Martabak Ambun di Payakumbuh - Ahmad Zulfikri; M. Wily Mahmuda; Sularno Sularno (CV. ITTC INDONESIA, 2025)
Martabak Ambun MSME is a local culinary business focusing on sweet and savory martabak products. As a growing enterprise at the regional level, Martabak Ambun faces challenges in expanding its market, building brand identity, and increasing competitiveness. This community service program aims to strengthen branding and digital marketing through training and mentoring on promotional strategies. The methods applied include observation, interviews, training on social media utilization, and implementation of digital content design. The results show an improvement in MSME understanding of branding strategies, the use of digital platforms (Instagram, Facebook, TikTok), and increased consumer engagement. Thus, empowering Martabak Ambun through digital marketing strategies has proven effective in enhancing the competitiveness of local culinary businesses.